2019
DOI: 10.14233/ajchem.2019.22146
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of Xanthan Gum and Carboxymethyl Cellulose on Physical and Sensory of Cloudy Asparagus Juice using Response Surface Methodology

Abstract: This study aims to investigate the effect of xanthan gum and carboxymethylcellulose on physical and chemical qualities of green asparagus juice. We adopted the surface-response method and the CCD experiment design with respect to three response variables including stability, viscosity and colour of the product. It was revealed that both xanthan gum and carboxymethylcellulose concentrations are both positively correlated with viscosity and stability of the product. In addition, the coefficient of the interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Table 3 shows that the viscosities of all the formulations of Improved-FRDFD-dH 2 O were significantly different from the control FRDFD-dH 2 O, in which the viscosity of the Improved-FRDFD-dH 2 O increased with increasing concentration of XG or CMC added. This phenomenon can be explained by the higher concentration of XG or CMC provided a higher number of hydroxyl (-OH) groups to interact, collide and form hydrogen bonds with the water molecules in the drink, therefore leading to a rapid rise in the viscosity [ 17 , 23 , 24 ]. At fixed 0.50 % CMC, increasing XG concentration from 0.30 to 0.50 % successfully elevated the viscosity of the drink between 142-fold and 260-fold (from 1.55 cP to minimally 220.46 cP and maximally 403.73 cP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 3 shows that the viscosities of all the formulations of Improved-FRDFD-dH 2 O were significantly different from the control FRDFD-dH 2 O, in which the viscosity of the Improved-FRDFD-dH 2 O increased with increasing concentration of XG or CMC added. This phenomenon can be explained by the higher concentration of XG or CMC provided a higher number of hydroxyl (-OH) groups to interact, collide and form hydrogen bonds with the water molecules in the drink, therefore leading to a rapid rise in the viscosity [ 17 , 23 , 24 ]. At fixed 0.50 % CMC, increasing XG concentration from 0.30 to 0.50 % successfully elevated the viscosity of the drink between 142-fold and 260-fold (from 1.55 cP to minimally 220.46 cP and maximally 403.73 cP).…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained agree with the previously published studies [ 32 , 33 ], whereby the incorporation of hydrocolloids will affect the competition for the water between the solutes. As the hydrocolloid concentrations increased, more hydroxyl groups were present, which subsequently increased the competition between the added hydrocolloids and the hydrophilic molecules in the drink, thereby inter-chain bonding promoted and significantly decreased the water activity in the fruit juice or filling [ 17 , 23 ]. Nonetheless, the water activity range (0.968–0.975) of all the Improved-FRDFD-dH 2 O formulations in this study remained near to that of a standard fruit juice/drink, around 0.97 [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, several studies on extraction of antioxidants from herbs have shown that temperature, time, and solvent/material ratio had a great influence on polyphenol content and antioxidant activity of extracts, in which each different material source required different temperature, time, and optimal solvent/extraction ratio. 22 Optimization of the obtained function with respect to maximal TPC yielded the following optimal values: X 1 = 56.0 (%), X 2 = 38.0 (mL/g), and X 3 = 67.2 (min), corresponding with optimal TPC of 2.8 mg GAE/g DW. Confirmation experiments were carried out in triplicate using the above optimal conditions, resulting in polyphenol content of 2.9 ± 0.071 mg GAE/g DW, which was approximately 2.6% higher, as compared with the TPC predicted from the model.…”
Section: Optimization Of Tpc Of the Cjr Extract Via Rsmmentioning
confidence: 99%
“…Moreover, the combination of 0.1% xanthan and CMC resulted in a favorable synergistic effect on viscosity (8.26 Pa•s), which may be because they carry the same negative charges that lead to coagulation and, ultimately, International Journal of Food Science an increase in viscosity. The free movement of the hydroxyl groups in the solution increases their affinity for water molecules to form a hydrophilic compound, leading to swelling and increased viscosity [59]. However, this effect was not considered significant in the resulting model.…”
Section: Densitymentioning
confidence: 99%